Race and Ethnicity Do Not Clinically Associate with Quality of Life Among Patients with Chronic Severe Pain in a Federally Qualified Health Center. Issue 7 (10th May 2017) - Dhingra, Lara; Schiller, Robert; Teets, Raymond; Nosal, Sarah; Rodriguez, Sandra; Cruciani, Gabriel; Barrett, Malcolm; Ginzburg, Regina; Ahmed, Ebtesam; Wasser, Thomas; Chen, Jack; Shuman, Saskia; et al.
Abstract: Objective: Previous research suggests that race/ethnicity predicts health-related quality of life (HRQL) in chronic pain populations but has not examined this in community settings. This study evaluated this association in 522 community-dwelling patients with chronic pain treated at a Federally Qualified Health Center (FQHC). Design: Cross-sectional secondary analysis. Setting: Six practice sites of an FQHC in New York. Subjects: One hundred forty-two non-Hispanic blacks, 121 non-Hispanic whites, 219 Hispanics, and 40 classified as "other" with severe chronic pain. Methods: Patients with chronic severe pain (three or more months with worst pain ≥ 4/10 or T-score > 60.5 on the Patient-Reported Outcomes Measurement Information System pain interference tool) were interviewed as part of a clinical trial. Race/ethnicity and other potential predictors of HRQL were assessed. Results: Mean age was 53.0 years, and 70.1% were women; 62.8% earned less than $10, 000 per year, and 22.8% were Spanish-speaking with low acculturation. Mean worst pain during the past week was 8.6/10, and 39.6% used opioids. In multivariate analyses, race/ethnicity was not significantly associated with mental HRQL. Hispanics had significantly lower physical HRQL than non-Hispanic whites or blacks, but this difference was not clinically meaningful (mean T-scores = 33.9 [Hispanics], 35.8 [non-Hispanic whites], and 35.6 [non-Hispanic blacks]). Mental HRQL was predicted by depression, anxiety, pain disability, income, and physical HRQL; physical HRQL was predicted by race/ethnicity, anxiety, pain disability, age, care satisfaction, and mental HRQL. Conclusions: Race/ethnicity does not explain important variation in HRQL reported by diverse patients with chronic pain. Psychological distress, pain disability, age, and socioeconomic status predicted this health outcome. Future studies may clarify modifiers of these associations to guide treatment in FQHC populations.